PENGEMBANGAN LITERASI DINI PADA ANAK USIA 4-6 TAHUN MELALUI BERMAIN HURUF DAN ANGKA - Monica Arningsari; Arri Handayani; Dini Rakhmawati (STKIP Subang, 2023)
The purpose of writing this article is to provide all readers with an understanding of the importance of early literacy in children aged 4-6 years in developing all aspects of development that can be integrated with all learning activities. Some people's views on early literacy are too high so that early literacy is linked to academic achievement at the elementary school level. As a result, early literacy in children aged 4-6 years or what is often referred to as preschool age may be ignored or considered less significant than academic readiness at a higher level. This has resulted in the view that literacy in children aged 4-6 years is reading and arithmetic. Many people also think that children learn by writing and calculating using worksheets or books. The many inaccurate assumptions about early literacy are very inconsistent with the basic principles of learning for children aged 4-6 years, which are still considered early childhood. Several alternative solutions to problems related to misunderstanding of early literacy can be done by returning to the principles of learning in early childhood, one of which is playing. In this case the author chose to play with letters and numbers which can be used for early literacy skills in children aged 4-6 years.